Parameter matching and braking performance advantage study for all-electric independent driving and braking electric vehicle with four wheels. (26th May 2019) - Yang, Kun; Wang, Jie; Tan, Di; Zhang, Xueyi; Liu, Jishun
All-electric integrated brake system is the feature for all-electric independent driving and braking electric vehicle with four wheels (AEIDBEV). Based on its advantages, an integrated simulation platform for parameter matching and performance verification is built. The vehicle control strategy is given. The results of simulation show that all-electric integrated brake system can meet the driver's braking demand and has three advantages. The first is that its braking effectiveness is slightly better than pure mechanical brake system. The second is work time and torque capacity for electromechanical brake (EMB) can be reduced remarkably. This provides a basis for optimising EMB. The third is that it can improve vehicle economy obviously. AEIDBEV has obvious energy saving effect compared with no braking energy recovery scheme and coupled braking energy recovery scheme at three drive cycles of NEDC, Beijing and Changchun.